Identifying preferences for specific beef flavor characteristics - O'Quinn, Travis Gene, author; Belk, Keith E., advisor; Tatum, J. Daryl, advisor; Woerner, Dale R., committee member; Engle, Terry E., committee member; Chapman, Phillip L., committee member (Colorado State University. Libraries, 2012)
Descriptive sensory analysis of beef samples was conducted at culinary institutions in three regions of the United States to determine differences in beef flavor attributes and flavor preferences among 12 different beef product categories (treatments). Treatments were chosen specifically to permit identification and characterization of production-related beef flavor differences, including effects of USDA grade (Prime, Premium Choice, Low Choice, Select), cattle breed-type (Angus, Holstein, American Wagyu), finishing diet (grass-fed, corn-fed, barley-fed), use of growth technologies (non-implanted, implanted, implanted & fed β agonists), and postmortem aging method (wet-aged, dry-aged). Panelists (N = 307) rated ground strip loin samples from each treatment for 13 different flavor notes (beefy/brothy, browned/grilled, buttery/beef fat, nutty/roasted nut, earthy/mushroom, bloody/metallic, grassy, livery, fishy, sour, sweet, and bitter) and overall flavor desirability. Each sensory attribute was rated on a 10-cm, unstructured line scale with 0 cm verbally anchored at very low intensity for all flavors and dislike extremely for flavor desirability and 10 cm verbally anchored at very high intensity for all flavors and like extremely for flavor desirability. In addition, samples were analyzed to determine percentage chemical lipid, moisture, protein, and ash of raw products, fatty acid composition of cooked products, and quantities of volatiles produced during cooking. Of the factors analyzed, USDA Quality grade and finishing diet (grain-fed vs grass-fed) had the largest effects on beef flavor attributes. Differences in cattle-breed type (Angus vs Wagyu), grain source (corn vs barley), aging technique (dry-aged vs wet-aged), and use of growth technology (non-implanted vs implanted vs implanted & fed β agonists) had only minimal effects on flavor. Extending the wet-aging period from 14 to 46 d had a negative effect on flavor, producing samples that scored higher (P < 0.05) for sour flavor than all other treatments. Panelists preferred samples with flavors described as beefy/brothy, browned/grilled, buttery/beef fat, nutty/nutty roasted nut, and sweet, and disliked flavors identified as bloody/metallic, grassy, gamey, livery, fishy, sour, and bitter. Moreover, overall flavor desirability scores were positively correlated (P < 0.05) with the concentration of several monounsatured fatty acids including C12:1, C14:1, C16:1 c9, and C18:1 c9. Stearic acid (C18:0) concentration was negatively correlated (P < 0.05) with overall flavor desirability and positively correlated (P < 0.05) with bloody/metallic, grassy/hay like, gamey, livery, fishy, sour, and bitter flavors. The concentration of several polyunsaturated fatty acids including C18:2t (total), C18:3 n-3, and C22:5 n-3, were found highest (P < 0.05) in Organic grass-fed samples and were negatively correlated (P < 0.05) with overall flavor desirability. Overall flavor desirability was positively correlated (P < 0.05) with diacetyl (2, 3-butanedione), acetoin (3-hydroxy-2-butanone), 3-methyl butanal, and pentanal concentrations. Samples with higher concentrations of dimethyl sulfide were rated lower (P < 0.05) for overall flavor desirability. The concentrations of several volatile compounds were correlated with various beef flavors including beefy/brothy, buttery/beef fat, browned/grilled, earthy/mushroom, nutty/roasted nut, sour, bitter, and sweet.
Keywords: beef; fatty acids; flavor; sensory; SPME; volatiles